Electrochemical genosensor based on gold nanostars for the detection of Escherichia coli O157:H7 DNA. Issue 16 (31st March 2022) - Razmi, Nasrin; Hasanzadeh, Mohammad; Willander, Magnus; Nur, Omer
Abstract : Electrochemical genosensor based on gold nanostars for E. coli O157:H7 detection constructed. Application of GNSs along with SWV technique provided a fast response for DNA detection of E. coli O157:H7 with a low limit of quantification of 0.01 zM. Abstract : Escherichia coli O157:H7 ( E. coli O157:H7) is an enterohemorrhagic E. coli (EHEC), which has been issued as a major threat to public health worldwide due to fatal contamination of water and food. Thus, its rapid and accurate detection has tremendous importance in environmental monitoring and human health. In this regard, we report a simple and sensitive electrochemical DNA biosensor by targeting Z3276 as a genetic marker in river water. The surface of the designed gold electrode was functionalized with gold nanostars and an aminated specific sensing probe of E. coli O157:H7 to fabricate the genosensor. Cyclic voltammetry (CV) and square wave voltammetry (SWV) techniques were applied for electrochemical characterization and detection. The synthesized gold nanostars were characterized using different characterization techniques. The fabricated DNA-based sensor exhibited a high selective ability for one, two, and three-base mismatched sequences. Regeneration, stability, selectivity, and kinetics of the bioassay were investigated. Under optimal conditions, the fabricated genosensor exhibited a linear response range of 10 −5 to 10 −17 μM in the standard sample and 7.3 to 1 × 10 −17 μM in water samples with a low limit of quantification of 0.01 zM in water samples. The detection strategy based on silver plated gold nanostars and DNA hybridization improved the sensitivity and specificity of the assay for E. coli O157:H7 detection in real water samples without filtration. The detection assay has the advantages of high selectivity, sensitivity, low amounts of reagents, short analysis time, commercialization, and potential application for the determination of other pathogenic bacteria.